Analysis of the influence of economic policies on investment strategies in the Peruvian context - Copaja Conde, Marcos Juniors (2024)
The evaluation of the impact of economic policies on investment strategies within the Peruvian context emerges as a fundamental approach to understand how governmental decisions directly affect corporate investment practices. In this critical analysis, we examine how economic policies implemented in the country exert influence on the investment strategies of organizations, generating significant implications for financial decision-making and long-term yield optimization. The methodology employed is based on a comprehensive literature review exploring the interrelation between economic policies and investment strategies, emphasizing the need to consider macroeconomic factors, government regulations, and local market conditions when designing effective investment strategies. The study delves into the implementation of specific policies, evaluating their impact on investment attraction, financial stability, and the promotion of sustainable economic development. Key strategies are identified, such as diversifying investment portfolios in sectors favored by government policies, adapting to regulatory changes, and continuously assessing political risks. The result is that, despite the inherent challenges of economic policy variability, it is argued that companies that understand and proactively adapt to this context will not only mitigate risks but also capitalize on emerging opportunities.